Proliferating SPP1/MERTK-expressing macrophages in idiopathic pulmonary fibrosis. Issue 2 (22nd August 2019) - Morse, Christina; Tabib, Tracy; Sembrat, John; Buschur, Kristina L.; Bittar, Humberto Trejo; Valenzi, Eleanor; Jiang, Yale; Kass, Daniel J.; Gibson, Kevin; Chen, Wei; Mora, Ana; Benos, Panayiotis V.; et al.
A comprehensive understanding of the changes in gene expression in cell types involved in idiopathic pulmonary fibrosis (IPF) will shed light on the mechanisms underlying the loss of alveolar epithelial cells and development of honeycomb cysts and fibroblastic foci. We sought to understand changes in IPF lung cell transcriptomes and gain insight into innate immune aspects of pathogenesis. We investigated IPF pathogenesis using single-cell RNA-sequencing of fresh lung explants, comparing human IPF fibrotic lower lobes reflecting late disease, upper lobes reflecting early disease and normal lungs. IPF lower lobes showed increased fibroblasts, and basal, ciliated, goblet and club cells, but decreased alveolar epithelial cells, and marked alterations in inflammatory cells. We found three discrete macrophage subpopulations in normal and fibrotic lungs, one expressing monocyte markers, one highly expressing FABP4 and INHBA (FABP4 hi ), and one highly expressing SPP1 and MERTK (SPP1 hi ). SPP1 hi macrophages in fibrotic lower lobes showed highly upregulated SPP1 and MERTK expression. Low-level local proliferation of SPP1 hi macrophages in normal lungs was strikingly increased in IPF lungs. Co-localisation and causal modelling supported the role for these highly proliferative SPP1 hi macrophages in activation of IPF myofibroblasts in lung fibrosis. These data suggest that SPP1 hi macrophages contribute importantly to lung fibrosis in IPF, and that therapeutic strategies targeting MERTK and macrophage proliferation may show promise for treatment of this disease. By single-cell RNA-sequencing we identify three discrete pulmonary macrophage subsets, including one expressing highly upregulated SPP1 and proliferating in fibrotic IPF lower lobes, accompanied by marked deposition of osteopontin in the matrix http://bit.ly/2wIRNqF